Synthesis of Solid Acid Catalyst from Fly Ash for Eugenol Esterification - Nur Hidayati; Titik Pujiati; Elfrida B. Prihandini; Herry Purnama (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
A series of fly ash-based heterogeneous acid catalysts were prepared by chemical and thermal treatment. Fly ash was chemically activated using sulfuric acid and followed by thermal activation. Characterization methods of XRD, BET, SEM-EDX, and the performance in esterification of eugenyl acetate production was carried out to reveal the physical and chemical characteristics of prepared catalysts. Activated catalyst showed high silica content (96.5%) and high BET surface area of 70 m2.g-1. The catalyst was proven to be highly active solid acid catalyst for liquid phase esterification of eugenol with acetic acid yielding eugenyl acetate. A yield of 43-48% was obtained with activated fly ash catalysts for 90 minutes reaction. These catalysts may replace beneficially the conventional homogenous liquid acid to the eco-friendly heterogeneous one.